Systematic Review: Service Learning and Development of Translation-Related Linguistic Competences - Morales Santibáñez, Angela Patricia (2022)
This systematic review was aimed at establishing the main characteristics of service learning projects that were designed to develop professional linguistic competences in university students involving a translation modality. The information collected will be specifically used as a guideline for the design of service-learning projects that facilitate the development of the translation competence in students of Chilean undergraduate translation programs. The review was carried out at the Web of Science data base and included papers published from 2015 to 2020. The content of the papers was reviewed in order to select those which gave account of empirical studies about the didactic use of service learning. 20 papers were considered suitable for inclusion and a data matrix was built to facilitate the systematic analysis of data sets. The results showed the context in which service learning projects were implemented, the educational area, the service tasks and the instruments used to measure their effects on students. The analysis led to the conclusion that translation tasks can be related to the delivery of community services which can also facilitate the development of linguistic and cultural competences among other abilities. The results also showed a correlation between students’ motivation and the construction of a new professional identity that makes them aware of their role in the battle against inequality. This review is aimed at establishing a theoretical foundation for the design of service projects that produce similar effects in Chilean university translation students by building mutually beneficial relationships between students and the community.